Tradisi Adat Ngayikka di Desa Negeri Kaya Kecamatan Tanjung Sakti Pumi Kabupaten Lahat - Okpini, Shelli; Hera, Treni; Sepdwiko, Deria (ANTHOR: Education and Learning Journal, 2022)
This study aims to describe the traditional Ngayikka tradition in Negeri Kaya Village, Tanjung Sakti District, PUMI, Lahat Regency. This study uses qualitative methods using observation techniques, interview techniques, and documentation techniques. The object in this study is the Ngayikka traditional tradition, the Ngayikka traditional tradition is one of the traditions originating from Tanjung Sakti District, PUMI, Lahat Regency which is one of Indonesia's cultural treasures and the research subjects are girls who are in Gadiska (Ngayikka) in the Indonesian language. Indonesia. Lahat area. The results of this study explain that the form of presenting the Ngayikka traditional tradition is recognized by the people of Tanjung Sakti, Lahat Regency, because the Ngayikka custom is still practiced every time they want to circumcise a girl (Ngayikka) until now. The persistence of the Ngayikka traditional tradition to this day, because this custom has become a hereditary tradition carried out by every girl entering school age known as Ngayikka (Ngayikka).